UPAYA PENCEGAHAN FRAUD PADA BANK BERPLAT MERAH YANG MERUGIKAN KEUANGAN NEGARA (Jurnal Magister Hukum Perspektif, 2021)
Fraud can occur anywhere and anytime including in red-plated banks (State-Owned Banks). As a place of money turnover, banking cannot be separated from criminal acts both general, civil, and corruption crimes because the Bank has a position that is vulnerable to abuse of authority either by employees on the front line such as tellers, costumer services, loan services or by branch heads even on the Board of Directors. The formulation of the issue raised is how the form of fraud prevention efforts, especially in State-Owned Banks related to the rescue of assets and wealth, is indicated to be detrimental to the country's finances. The type of research used is juridical-normative which is one of the legal research methods obtained by analyzing a legal problem through laws and regulations and related literature. The results found prevention efforts consist of technical and moral aspects and integrity. Technical aspects can be through (1) Double-check customer data, (2) Rewarding Loophole Inventors, (3) Creating good internal controls, (4) Transparency to Customers, (5) Increasing Personnel Supervision, (6) Implementing e-KYC, (7) Whistleblowers. Moral and integrity aspects must be owned by every party involved in activities in the bank. In addition, Law Enforcement Officials (APH) must also comply with the implementation of the commercial bank anti-fraud strategy that has been regulated in the POJK for the Rescue of State Finances and State Assets and National Economic Recovery. Keywords: Prevention, fraud, bank.